INTRODUCTION TO NATIONALISM VALUES THROUGH MEDIA COLORING PICTURES IN BIPA LEARNING AT UPN VETERAN JAWA TIMUR - Dewi Puspa Arum; Laksmi Diana; Eni Nurhayati; Natalia Desy Anggraeni (Jurnal Scientia, 2021)
UPN Veterans East Java as a State Defense Campus is a manifestation of the implementation of Article 27 paragraph 3 of the 1945 Constitution regarding the form of a state defense system to deal with non-military threats. One of the actual forms in general is the existence of Indonesian Language courses for Foreign Speakers (BIPA). The values ​​of nationalism can be traced to the five precepts contained in Pancasila, namely, Belief in One God, just and civilized humanity, Indonesian unity, democracy led by wisdom in representative deliberation, and social justice for all Indonesian people. This research is a qualitative descriptive study with the application of practical methods. The practical method was chosen because it is in accordance with BIPA learning activities, namely coloring pictures related to state symbols, culture, customs, and traditions in Indonesia that contain nationalism values. The unit of research analysis is the values ​​of nationalism originating from Pancasila in BIPA learning for Yemeni students at UPNVJT. Triangulation of data sources was used as data validation. The research data analysis technique used was the interactive model of Miles and Huberman (1984). The results of the research related to the introduction of the values ​​of nationalism include the introduction of the 5 precepts in Pancasila, the introduction of symbols and symbols of Pancasila, the meaning of Pancasila and its relation to nationalism, as well as attitudes that reflect nationalism during Yemeni students study at UPN Veterans, East Java. Obtained results of research related to the stages in the practical method with coloring pictures media, namely, (1) Delivery of the initial objectives, (2) Explanation of practical material, (3) Demonstration of how to work, (4) Practice exercises/simulations, (5) Transfer training to test students' understanding regarding the introduction of nationalism values.